Pengaruh Computer Anxiety Terhadap Keahlian Pemakai Komputer dengan Internal Locus Of Control sebagai Variabel Moderasi - Harimurti, Fadjar; Saptantinah Puji Astuti, Dewi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 2 (2016), 2017)
This study aims (1) to analyze the effect of computer anxiety in using accounting software towards the last users’ skill (2) to analyze the effect of computer anxiety in using accounting software towards the last users’ skill by using internal locus of control as a moderating variable. The population of the study is all students of the economics faculty majoring in accounting at UNISRI Surakarta. This study uses 46 students as samples who has met the purposive criterias such as they are taking computer accounting course on odd semester of the academic year 2015/2016. Hypothesis was tested using regression analysis with absolute residual. The results show that (1) computer anxiety in using accounting software has negative affect towards the last users’skill (students of accounting program in economics faculty of UNISRI Surakarta). (2) internal locus of control moderates the effect of computer anxiety in using accounting software towards end user skill (students of accounting program in economics faculty of UNISRI Surakarta).
Keywords: computer anxiety in using accounting software, internal locus of control, end user computing skilled